Oxysterols Increase Inflammation, Lipid Marker Levels and Reflect Accelerated Endothelial Dysfunction in Experimental Animals - Tomasz Wielkoszyński; Jolanta Zalejska-Fiolka; Joanna K. Strzelczyk; Aleksander J. Owczarek; Armand Cholewka; Marcin Furmański; Agata Stanek (Hindawi Limited, 2018)
Objective. Oxidized cholesterol derivatives are thought to exert atherogenic effect thus adversely affecting vascular endothelium. The aim of the study was to assess the effect of 5α,6α-epoxycholesterol on experimentally induced hypercholesterolemia in rabbits, and the levels of homocysteine (HCY), asymmetric dimethylarginine (ADMA), paraoxonase-1 (PON-1), and inflammatory parameters (IL-6, TNF-α, CRP). Material and methods. The rabbits were divided into 3 groups, 8 animals each, and fed with basic fodder (C), basic fodder plus cholesterol (Ch) or basic fodder plus 5α,6α-epoxycholesterol, and unoxidized cholesterol (ECh). Serum concentrations of studied parameters were determined at 45-day intervals. The study was continued for six months. Results. We demonstrated that adding 5α,6α-epoxycholesterol to basic fodder significantly affected lipid status of the experimental animals, increasing total cholesterol and LDL cholesterol levels, as well as HCY and ADMA levels, whilst leaving the PON-1 activity unaffected. Additionally, the ECh group presented with significantly higher concentrations of inflammatory biomarkers (IL-6, TNF-α, and CRP). In the Ch group, lower yet significant (as compared to the C group) changes of levels of studied parameters were observed. Conclusion. Exposure of animals with experimentally induced hypercholesterolemia to 5α,6α-epoxycholesterol increases dyslipidaemia, endothelial dysfunction, and inflammatory response.